Unmanned aerial vehicle design for disaster victim search and rescue operation using wireless sensor network localization - Hutabarat, Fajar Sam; Sitanggang, Imanuel Maurice Darmawan; Damanik, Joy Andrew Immanuel; Knight, Guntur Petrus Boy; Sagala, Albert (Institute of Advanced Engineering and Science, 2022)
The search for disaster victims carried out by search-and-rescue (SAR) team mainly uses traditional methods, which are considered to take much time and effort, and pose a high risk for the search team and the victim. Based on this problem, we conducted research to assist disaster victim search. In this research, we designed a system using passive infrared (PIR) sensors to detect and measure the direction angle of the victim. Given the direction angle from different observation points’ perspectives, we determine the victim’s position using the triangulation method. we also designed a quadcopter unmanned aerial vehicle (UAV) to carry this sensor system across the disaster area. For monitoring purposes, a local website was designed to display data generated by the system. Based on test results, the system can determine a victim’s position with a distance difference of less than 5 m. The system can search victim in an empty land ±35 m×15 m wide in 14 minutes 20 seconds. The data monitoring system also displayed the victim’s position, the position of the observation points, and the UAV’s flight path.